FRIENDSHIP IN GROOM’S FORREST GUMP - Imanuel Kevins Mangero; Agustine Clara Mamentu; Imelda S. Lolowang (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of the research was to reveal the friendship in Winston Groom’s “Forrest Gump”. The author uses a qualitative method to this research. The data collected in this research from two sources,primary sources and secondary sources. Primary sources is Groom’s Forrest Gump and secondary sources are the other books and data from internet that related to this research. Psychological approach is applied in analyzing the data to reveal the friendship in the novel. The result of this research is contribute the values of human life,especially about friendship in social interaction,respect each other,and build a good relationship in people life. Especially the friendship between Forrest and his bestfriend which shows loyalty, sacrifice and mutual understanding,because the story of the novel reflected about the human life especially about the friendship. The implication of this study is to enrich the knowledge of the writers and the readers about the main character’s friendship that in Groom's Forrest Gump. Moreover, it can be a reference for the students of English Department who are attracted to observe the similar research. Therefore, this research can conclude the novel, Forrest Gump, to show the forms of the friendship of the main character.